The view of mathematics education as science - Friska Ledina Situngkir; Izwita Dewi (SAINTIS Publishing, 2022)
This paper will discuss the view of mathematics education as science. This study is the result of a variety of relevant literature related to mathematics education as a science in a scientific discipline. Philosophically, mathematics is considered as the queen of science used by humans in everyday life. While knowledge itself is closely related to philosophy, where these two terms cannot be separated from each other. The science of studying natural phenomena itself. Science is the product of epistemology, ontology, and axiology. Philosophy and science are two similarities in that both seek the truth. A person who seeks the truth is a philosopher or philosopher. The source of philosophy is man, reason, and the human heart. For example, mathematics. Mathematics is a science about reasoning, about patterns and mathematics is the queen of science and at the same time a servant of science. Mathematics education is a mathematics lesson that makes students build logical thinking and build mathematical knowledge.